Association of Body Mass Index with Endothelial Function in Asian Men. (1st February 2021) - Kajikawa, Masato; Maruhashi, Tatsuya; Kishimoto, Shinji; Hashimoto, Haruki; Takaeko, Yuji; Yamaji, Takayuki; Harada, Takahiro; Hashimoto, Yu; Han, Yiming; Kihara, Yasuki; Hida, Eisuke; Chayama, Kazuaki; et al.
Abstract: Background: The association of body weight with cardiovascular events is still controversial. We evaluated the relationship between body mass index (BMI) and endothelial function. Methods: We measured flow-mediated vasodilation (FMD) and BMI in 7682 men. All participants were divided into four groups by BMI: underweight (<18.5 kg/m 2 ), normal weight (18.5 to 24.9 kg/m 2 ), overweight (25.0 to 29.9 kg/m 2 ), and obesity (≥30.0 kg/m 2 ). Results: Multiple logistic regression analysis revealed that overweight (OR: 1.30, 95% CI: 1.14–1.47; P  < 0.001) and obesity (OR: 1.40, 95% CI: 1.09–1.80; P  = 0.009) were associated with an increased risk of a low quartile of FMD. In 5571 younger adults (<60 years), overweight (OR: 1.34, 95% CI: 1.16–1.55; P  < 0.001) and obesity (OR: 1.37, 95% CI: 1.04–1.81; P  = 0.03) were associated with an increased risk of a low quartile of FMD, and underweight (OR: 0.56, 95% CI: 0.35–0.89; P  = 0.01) was associated with a reduced risk of a low quartile of FMD. In 2111 older adults (≥60 years), underweight (OR: 2.16, 95% CI: 1.22–3.80; P  = 0.008) was associated with an increased risk of a low quartile of FMD, and overweight and obesity were not associated with a risk of a low quartile of FMD. Conclusions: In Asian men, endothelial function was impaired in the overweight and obesity groups compared with that in the normal weight group. The risk for endothelial dysfunction was higher in obese younger adults than in obese older adults. The association of BMI with endothelial function may be different in young and elderly men. Clinical Trial Registration Information: http://www.umin.ac.jp (University Hospital Medical Information Network Clinical Trials Registry) (UMIN000012952). Highlights: The risk for endothelial dysfunction was higher in obese younger adults than in obese older adults. Obesity paradox was seen in the endothelial function in the elderly. Endothelial function was better in underweight younger adults than in the normal weight group. Endothelial function was impaired in underweight older adults compared with that in normal weight group. The association of BMI with endothelial function may be different by age.